High-throughput RNAi screening: methods and protocols - Azorsa, David O.; Arora, Shilpi (Methods in molecular biology, 2016)
Establishing an Infrastructure for High-Throughput Short-Interfering RNA Screening -- Optimization of Transfection Conditions for siRNA Screening -- High Throughput siRNA Screening Using Reverse Transfection -- Genome-Wide siRNA Screening Using Forward Transfection: Identification of Modulators of Membrane Trafficking in Mammalian Cells -- Pooled shRNA Screening in Mammalian Cells as a Functional Genomic Discovery Platform -- A Protocol for a High-Throughput Multiplex Cell Viability Assay -- RNAi Screening of Leukemia Cells Using Electroporation -- Self-Assembled Cell Microarray (SAMcell) for High-Throughput RNAi Screening -- In Vitro Pooled shRNA Screening to Identify Determinants of Radiosensitivity -- Three-Dimensional Spheroid Cell Culture Model for Target Identification Utilizing High-Throughput RNAi Screens -- In Vitro High Throughput RNAi Screening to Accelerate the Process of Target Identification and Drug Development -- High-Throughput, Liquid-Based Genome-Wide RNAi Screening in C. elegans -- Design and Methods of Large-Scale RNA Interference Screens in Drosophila -- Genome-Wide RNAi Screening in C. elegans for Aging and Innate Immunity -- RNAi-Assisted Genome Evolution (RAGE) in Saccharomyces cerevisiae -- RNAi Screening in Spodoptera frugiperda -- Morphology and Gene Expression Screening with Morpholinos in Zebrafish Embryos -- Live Cell Microscopy-Based RNAi Screening in the Moss Physcomitrella patens -- Data Analysis For High Throughput RNAi Screening. .